Two new species of Sycorax (Diptera: Psychodidae: Sycoracinae) from the Oriental Region - Ježek, Jan; Wahab, Rodzay Abdul; Ševčík, Jan; Wahab, Rodzay Abdul; Ševčík, Jan (Zootaxa, 2015)
Two new species of Sycorax Haliday in Curtis, 1839 are described from Ulu Temburong National Park in Brunei Darussalam: Sycorax konopiki sp. nov. and S. tomkineana sp. nov. Both species were found resting on two frog species: Ansonia leptopus (Günther, 1872) and A. longidigita Inger, 1960. Differential diagnoses for males are included and morphological characters illustrated. Possible host associations of the new species are briefly discussed. DNA barcode sequence (COI) for Sycorax konopiki sp. nov. is also provided.